2010
DOI: 10.22146/ijc.21467
|View full text |Cite
|
Sign up to set email alerts
|

ANTICANCER ACTIVITY OF CALANONE ON HeLa CELL LINE

Abstract: Calanone (coumarin derivate compound), isolated from Calophyllum sp. had been shown to have cytotoxic activity on leukemia L1210 cell line with IC50 = 59.40 mg/mL. Calanone presumed have anticancer activity on HeLa cervical carcinoma cell. This study was conducted to investigate the cytotoxic and apoptotic activity of calanone and its effect to p53 and p21 expression on HeLa cervical carcinoma cell. Cytotoxic assay of calanone was performed on HeLa cell line, using MTT assay. Apoptotic assay was performed on H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…After 24 h, cells were treated with C. betacea extract (IC 50 values), doxorubicin (8 µg/ml) that served as positive control and culture medium (1% DMSO) that served as negative control for 24, 48 and 72 h. After exposure of grown cells in the extract, cells were washed with phosphate buffer saline (PBS) and harvested by centrifugation (2000 rpm for 5 min) and washed twice with PBS. The pellet (10 µl) were mixed with 5 µl (10 µg/ml) acridine orange and 5 µl (10 µg/ml) PI and observed under fluorescence microscope (Ekowati et al 2010). …”
Section: Methodsmentioning
confidence: 99%
“…After 24 h, cells were treated with C. betacea extract (IC 50 values), doxorubicin (8 µg/ml) that served as positive control and culture medium (1% DMSO) that served as negative control for 24, 48 and 72 h. After exposure of grown cells in the extract, cells were washed with phosphate buffer saline (PBS) and harvested by centrifugation (2000 rpm for 5 min) and washed twice with PBS. The pellet (10 µl) were mixed with 5 µl (10 µg/ml) acridine orange and 5 µl (10 µg/ml) PI and observed under fluorescence microscope (Ekowati et al 2010). …”
Section: Methodsmentioning
confidence: 99%
“…While IFNα-2b expressed in P. pastoris inhibited 44% breast cancer (MCF) cell proliferation at 20 nmol/L [33]. The IC 50 value of 5-fluorouracil (5-FU) as a drug for colorectal cancer was reported at 129.29 µg/ml [34]. The result showed that a cytotoxicity of purified IFNα-2b was also comparable with the commercial drug.…”
Section: Anticancer Activity Of Recombinant Ifnα-2b Against Colorectamentioning
confidence: 99%
“…Moreover, the biological evaluations of coumarins revealed that the engrossment of innumerable pathways via coumarins acts as anticancer agents. They target a number of pathways in cancer like as kinase inhibition, cell cycle arrest, heat shock protein (HSP90) inhibition, angiogenesis inhibition, monocarboxylate transporters inhibition, antimitotic activity, carbonic anhydrase inhibition, telomerase inhibition, aromatase inhibition, and sulfatase inhibition ( Ekowati et al, 2010 ; Li et al, 2010 ; Wang et al, 2011 ; Bhattarai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%